2017
DOI: 10.7150/thno.20797
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometry-assisted gel-based proteomics in cancer biomarker discovery: approaches and application

Abstract: There is a critical need for the discovery of novel biomarkers for early detection and targeted therapy of cancer, a major cause of deaths worldwide. In this respect, proteomic technologies, such as mass spectrometry (MS), enable the identification of pathologically significant proteins in various types of samples. MS is capable of high-throughput profiling of complex biological samples including blood, tissues, urine, milk, and cells. MS-assisted proteomics has contributed to the development of cancer biomark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 218 publications
(220 reference statements)
0
34
0
1
Order By: Relevance
“…Prostate cancer is one of the most common malignancies among men, with a global incidence of 1.3 million new cases every year [ 199 ]. While prostate cancer may require minimal or even no treatment at early stages, metastasizing to the bone is a serious concern for about 65–80% of advanced stage cases [ 200 , 201 ]. The five-year survival rate of prostate cancer patients with localized prostate cancer has increased to over 90% with improved technologies for the treatment at an early stage; however, once the tumor cells metastasize, the 5-year survival rate substantially decreases to only 28% [ 202 ].…”
Section: Clinical Serum/plasma Proteomics and Molecular Signaturesmentioning
confidence: 99%
“…Prostate cancer is one of the most common malignancies among men, with a global incidence of 1.3 million new cases every year [ 199 ]. While prostate cancer may require minimal or even no treatment at early stages, metastasizing to the bone is a serious concern for about 65–80% of advanced stage cases [ 200 , 201 ]. The five-year survival rate of prostate cancer patients with localized prostate cancer has increased to over 90% with improved technologies for the treatment at an early stage; however, once the tumor cells metastasize, the 5-year survival rate substantially decreases to only 28% [ 202 ].…”
Section: Clinical Serum/plasma Proteomics and Molecular Signaturesmentioning
confidence: 99%
“…During the following years, several milestones for MS in the clinics (for analytes other than proteins) were achieved such as tandem MS for newborn screening in 1990. The clinics may have been embracing the MS methodology slowly as discussed elsewhere 57 compared to the research community, which is now, more than ever, relying on MS data prior to concluding (several journals even require MS data to publish results for certain analytes 56 ). Even though several analytical platforms have previously been used for protein analyses, now the proteomic investigations are mostly carried out with MS and are divided into two main categories, targeted and non-targeted analysis.…”
Section: Mass Spectrometry In Protein Analysismentioning
confidence: 99%
“…With the regulatory events often occurring at gene promoters, we speculated that some tumor-specific cellular factors might bind specifically to the CLC-3 promoter to upregulate CLC-3 expression. Therefore, an optimal promoter probe was synthesized to pull down CLC-3 promoter-binding proteins [ 32 , 33 ]. Our study demonstrated that XRCC5 bound the CLC-3 promoter, and increased combination was observed in GC cells, suggesting that this increased binding might be a promoting factor of CLC-3 overexpression.…”
Section: Discussionmentioning
confidence: 99%